2021
DOI: 10.3390/bioengineering8110187
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered System for High Throughput Screening of Kv1 Ion Channel Blockers

Abstract: Screening drug candidates for their affinity and selectivity for a certain binding site is a crucial step in developing targeted therapy. Here, we created a screening assay for receptor binding that can be easily scaled up and automated for the high throughput screening of Kv channel blockers. It is based on the expression of the KcsA-Kv1 hybrid channel tagged with a fluorescent protein in the E. coli membrane. In order to make this channel accessible for the soluble compounds, E. coli were transformed into sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several binding assays were applied in the past to investigate channel protein and ligand interactions, such as fluorescent and radioligand-based techniques. One of the earliest approaches to study interactions between recombinantly produced channel proteins and ligands required the immobilization of the target protein onto an adhesive surface such as CM5-dextrane; however, it also required the use of radioligands ( 30 , 44 , 55 ). A more convenient method is the traditional phage ELISA assay, in which the target protein is immobilized onto protein-binding 96-well polystyrene plates (such as MaxiSorp), and the toxin peptides are presented on the surface of M13 phages ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several binding assays were applied in the past to investigate channel protein and ligand interactions, such as fluorescent and radioligand-based techniques. One of the earliest approaches to study interactions between recombinantly produced channel proteins and ligands required the immobilization of the target protein onto an adhesive surface such as CM5-dextrane; however, it also required the use of radioligands ( 30 , 44 , 55 ). A more convenient method is the traditional phage ELISA assay, in which the target protein is immobilized onto protein-binding 96-well polystyrene plates (such as MaxiSorp), and the toxin peptides are presented on the surface of M13 phages ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that in addition to the turret region, part of the filter region is also responsible for selective ligand binding, therefore the validity of the T-only chimeras to predict relative binding affinities of potential ligand molecules might be limited ( 16 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ). Attempts to recombinantly produce active chimeras harboring both the turret and the filter region (denoted as T+F) of human Kv1.x channels in heterologous expression systems were unsuccessful due to poor expression and inaccurate assembly of monomers resulting in defective tetramers ( 34 , 44 ).…”
mentioning
confidence: 99%